THEMATIC GEOVISUALIZATION OF THE DATA PROFILE OF KALIGESING, PURWOREJO, CENTRAL JAVA - Sudaryatno, Sudaryatno; El-Yasha, Shafiera Rosa; 'Afifah, Zulfa Nur'aini (Forum Geografi, 2019)
The scientific field has a variety of purposes, one of which is the presentation of data and information which can be used by other parties to support their decision making. Moreover, the information is presented spatially. This research aims to map the data profile of Kaligesing district to establish the region?s potential through thematic geovisualization of its data profile, such as slopes, land use, livelihoods and population. The primary data were obtained from visual interpretation of remote sensing images to extract land use information, and DEM processing to extract slope information. Secondary data were provided by the Kaligesing district government. In order to build tiered spatial modelling, each thematic map was classified and weighted according to its contribution to the potential of the region. Based on this modelling, each village was given a compilation of weights, which were used as a basis for regional potential analysis. From the results of the thematic mapping, Kaligesing has three villages that have the potential for development in the agricultural, trade and service sectors, supported by the potential of human resources, and the abundant non-residential land available.